Characterization of the C5H11ORF96 gene in chickens: cloning, tissue distribution and investigation of its potential function in stress response regulation - Yiping Wan; Jiannan Zhang; Xiao Zhang; Jiliang He; Ningkun Shi; Yuanyou Li; Juan Li; Yajun Wang (Poultry Science)
Chicken is an important economic animal that encounter various stressors including high temperature, high stocking density, bacterial infections and transportation, etc. affecting the poultry production with serious economic loss. To be in response to the varied stimulus, the hypothalamic-pituitary-adrenal (HPA) axis is activated through the controlling of the synthesis and secretion of glucocorticoids (GCs). Present study characterized a novel gene C5H11ORF96, that demonstrated significant upregulation after the DEX injection in chicken, which simulates the stress stimulus. Our results showed that: (1) cC5H11ORF96 cDNA encodes a 120 amino acids protein, which shares high sequence identity with that of birds, mammals, reptiles, frogs and fish; (2) cC5H11ORF96 has a fully conserved RFKTQP motif and high proportion of serine, indicating its multiple potential phosphorylation sites; (3) cC5H11ORF96 is widely expressed in various chicken tissues, with high expression levels in the parathyroid gland, adrenal gland, and pituitary; (4) glucocorticoids (GCs) and stress significantly upregulate C5H11ORF96 mRNA and protein expression in the chicken pituitary and hypothalamus, suggesting its involvement in regulating stress response by influencing the negative feedback of GCs on the HPA axis in chickens. The characterization of the C5H11ORF96 gene in the chicken stress response provides potential targets for stress adaptability and poultry production. Meanwhile, our finding provides essential insights into the physiological functions of C11ORF96 gene in vertebrates.